2005
DOI: 10.2337/diabetes.54.7.2026
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Factors in a Model of Type 1 Diabetes Differentially Affect the Development of Insulitis and Overt Diabetes in Offspring

Abstract: Type 1 diabetes, a multifactorial disease involving genetic and environmental factors, results from the destruction of pancreatic ␤-cells. The maternal environment has been suggested to be important in the development of diabetes. To assess the role of maternal factors in the development of insulitis and overt diabetes, we transplanted pre-implantation stage embryos of nonobese diabetic (NOD) mice, a model of type 1 diabetes, into the uterus of each recipient. Recipients were ICR and DBA/2J mice without diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(50 citation statements)
references
References 32 publications
1
49
0
Order By: Relevance
“…Restriction of energy intake increases circulating corticosterone levels, which in turn enhances negative selection of potentially autoreactive CD4-CD8 cells in thymus [48]. Maternal undernutrition during gestation may also decrease transplacental transmission of islet antibodies, a process which can also contribute to diabetes in NOD mice [49]. While our experiment showed a significant effect of intrauterine undernutrition on the degree of insulitis in NOD mice, suggesting that immune responses are altered in our low-birthweight model, we did not measure anti-islet antibodies, corticosterone, lymphocyte numbers or activity, or cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Restriction of energy intake increases circulating corticosterone levels, which in turn enhances negative selection of potentially autoreactive CD4-CD8 cells in thymus [48]. Maternal undernutrition during gestation may also decrease transplacental transmission of islet antibodies, a process which can also contribute to diabetes in NOD mice [49]. While our experiment showed a significant effect of intrauterine undernutrition on the degree of insulitis in NOD mice, suggesting that immune responses are altered in our low-birthweight model, we did not measure anti-islet antibodies, corticosterone, lymphocyte numbers or activity, or cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…This was not the case when another maternal background like DBA/2 or ICR non-diabetes prone mice was used. 38 Moreover, NOD progeny from NOD mothers deficient in B cells or in B and/or T cells failed to develop diabetes supporting the possibility that maternal T and potentially B cells acquired during pregnancy and lactation might play a role in the development of auto-immune diabetes. 39 These data suggest that the maternal environment during fetal life can play a role in offspring's immunity later in life.…”
Section: Maternal Microchimerism May Trigger Allogeneic Responsesmentioning
confidence: 99%
“…It was reported that the change in immune response brought about by maternal environment involving pseudo-pregnant recipients and surrogate mothers induced this difference of progression to diabetes [6]. In addition, Greeley et al (2002) reported that NOD offspring implanted in mothers of a nonautoimmune strain were protected from spontaneous diabetes [4].…”
Section: Irs2mentioning
confidence: 99%
“…Onset of diabetes in non-obese diabetic (NOD) mice produced by embryonic transfer and surrogate nursing by ICR and DBA/2J strain mice was significantly suppressed in comparison with mice produced from pseudo-pregnant recipients and surrogate mothers using NOD mice [6]. It was reported that the change in immune response brought about by maternal environment involving pseudo-pregnant recipients and surrogate mothers induced this difference of progression to diabetes [6].…”
Section: Irs2mentioning
confidence: 99%
See 1 more Smart Citation